Carbon Aerogels for Environmental Clean‐Up. Issue 27 (27th May 2019) - Gan, Guoqiang; Li, Xinyong; Fan, Shiying; Wang, Liang; Qin, Meichun; Yin, Zhifan; Chen, Guohua
Abstract : Carbon aerogels are a fascinating three‐dimensional (3D) monolithic porous material with remarkable physicochemical properties, including low density, large surface area, abundant pore structure, high electrical conductivity, chemical stability, environmental compatibility, adjustable surface chemistry, as well as controllable structural features. These properties endow carbon aerogels with excellent adsorption and catalytic performance. Therefore, they are widely applied in environmental chemistry for removing pollutants like oils, toxic organic solvents, dyes, heavy metal ions in aquatic environments, and volatile organic compounds (VOCs), carbon oxides (CO2, CO), nitrogen oxide (NOx ), and hydrogen sulfide (H2 S) in the atmosphere. In this paper, the preparation processes of carbon aerogels are fully reviewed, and their applications for environmental clean‐up based on adsorption and catalytic action are thoroughly addressed. In each section, the most recent representative studies will be highlighted. Finally, the challenges, outlooks, and prospects in this emerging and promising research field will be briefly discussed. Abstract : Carbon aerogels have excellent properties including low apparent density, large specific surface area, abundant pore structure, high electrical conductivity, good chemical stability, environmental compatibility, as well as modifiable surface chemistry and controllable texture and structural features. Their applications as adsorbents and catalysts for environmental clean‐up have been reviewed.